Technological and economic aspects of electric vehicle charging in Hungary - Seres, László; Tamás, Péter (Advanced Logistic Systems - Theory and Practice, 2025)
One of the main barriers to the uptake of electric vehicles in Hungary is the infrastructure, which allows the transition to electric cars while maintaining the driving habits that have been established so far. The aim of this paper is to explore the technological and economic aspects of electric car charging, with a systematic review of the Hungarian and international literature, with a special focus on the Hungarian situation. The research compares the cost of charging electric vehicles with the fuel costs of conventional vehicles. Based on the results obtained, it will propose future research directions for strategic directions supporting sustainable transport, highlighting the role and future potential of solar systems.